2016
DOI: 10.1093/ecco-jcc/jjw069
|View full text |Cite
|
Sign up to set email alerts
|

Modified Two-stage Ileal Pouch-Anal Anastomosis Results in Lower Rate of Anastomotic Leak Compared with Traditional Two-stage Surgery for Ulcerative Colitis

Abstract: Patients with ulcerative colitis who received the modified two-stage IPAA had a significantly lower rate of anastomotic leak following pouch creation, compared with the traditional two-stage procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(64 citation statements)
references
References 42 publications
1
58
0
1
Order By: Relevance
“…The fourth period covered the years 2010 to 2013. 1757 patients identified from previous study [26] 67 with missing data 34 with data found Based on the between-hospital differences in average annual pouch procedures performed, we categorized hospital volume as very low (1-5 cases/year), low (6-10 cases/year), intermediate (11)(12)(13)(14)(15)(16)(17)(18)(19)(20) cases/year) and high (> 20 cases/year). For this categorization, we divided the total number of procedures performed at a department by the total number of calendar years in which pouch procedures were performed.…”
Section: Covariatesmentioning
confidence: 99%
See 1 more Smart Citation
“…The fourth period covered the years 2010 to 2013. 1757 patients identified from previous study [26] 67 with missing data 34 with data found Based on the between-hospital differences in average annual pouch procedures performed, we categorized hospital volume as very low (1-5 cases/year), low (6-10 cases/year), intermediate (11)(12)(13)(14)(15)(16)(17)(18)(19)(20) cases/year) and high (> 20 cases/year). For this categorization, we divided the total number of procedures performed at a department by the total number of calendar years in which pouch procedures were performed.…”
Section: Covariatesmentioning
confidence: 99%
“…The most important risk factors for pouch failure are pelvic sepsis [8][9][10][11], Crohn's disease (CD), chronic antibiotic-resistant pouchitis, and 'idiopathic' pouch dysfunction [9,12,13]. Currently, controversy exists as to the importance of timing of the restorative pouch procedure in relation to the colectomy [14] and the merits of temporary faecal diversion to reduce the risk of failure of the pouch are debated [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…(92) A recent study concluded that patients with the modified twostage IPAA reported significantly lower anastomotic leaks, despite suffering from more severe UC activity and higher preoperative use of steroids. (93) The advantage of the three-stage and the modified two-stage IPAA is that it can be performed in emergency settings as it allows time to improve the patients' nutritional status, treat anemia, and withdraw from immunomodulating medications before going through a more complex pelvic dissection with a high risk anastomosis. (92,94) Other studies concluded that the three-stage IPAA is associated with more intraoperative hemodynamic instability and lower use of immune modulators.…”
Section: Surgical Reconstruction For Ulcerative Colitismentioning
confidence: 99%
“…Some centers have attempted to abbreviate the hospital course of acute severe UC patients by performing a modified two-stage procedure (colectomy followed by IPAA and ileostomy takedown). Zittan et al[ 49 ] demonstrated significantly lower rates of anastomotic leak (4.6% vs 15.7%) when comparing modified 2-stage IPAA to the traditional 2-stage procedure (colectomy with pouch formation followed by ileostomy takedown). Swenson et al[ 50 ] demonstrated equivalent patient outcomes with significantly lower hospital cost in patients with resolved severe colitis after colectomy who underwent a modified two-stage IPAA vs a three-stage procedure.…”
Section: Staged Approachmentioning
confidence: 99%